Evaluation Of Burkholderia Sp. Usm (Jcm 15050) For The Production Of Copolymeric Polyhydroxyalkanoate Containing 3-Hydroxy-4- Methylvalerate Monomer - Lau, Nyok Sean (2013)
The nutrition-versatility of Burkholderia sp. strain USM (JCM 15050) has initiated the studies on the use of this bacterium for polyhydroxyalkanoate (PHA) production. This study was carried out to evaluate the ability of Burkholderia sp. USM (JCM 15050) and its transformant harboring the PHA synthase gene of Aeromonas caviae to incorporate a new type of PHA monomer, 3-hydroxy-4- methylvalerate (3H4MV). This monomer with methyl side chain is of interest since the monomer can prevent the deterioration of poly(3-hydroxybutyrate-co-3-hydroxy- 4-methylvalerate), P(3HB-co-3H4MV) during aging. To promote the accumulation of PHA containing 3H4MV monomer, 4-methylvaleric acid was provided as cocarbon source. The polymerization of 3H4MV monomer by Burkholderia sp. USM (JCM 15050) confirmed the ability of Burkholderia sp. USM (JCM 15050) synthase to accept CoA thioester of 3H4MV, a six-carbon atom monomer, as substrate. Various culture parameters such as concentrations of NR medium, fructose and 4- methylvaleric acid as well as harvesting time were manipulated to produce P(3HBco- 3H4MV) with different 3H4MV compositions. The structural properties of PHA containing 3H4MV monomer were investigated by using nuclear magnetic resonance (NMR) and fourier transform infrared spectroscopy (FTIR). The relative intensities of the bands at 1183 and 1228 cm-1 in the FTIR spectra enabled the rapid detection and differentiation of P(3HB-co-3H4MV) from other types of PHA.